Effect of emigration on the structural transformation of the economic community of West African states - Gniniguè, Moukpè; Tchalim, Tom-Irazou (DEMO, 2021)
The objective of this paper is to study the effect of emigration on the structural transformation of the Economic Community of West African States (ECOWAS). Structu- ral transformation is measured by the reallocation of labor from the industrial sector and services sector. The dynamic ordinary least squares method is used and has revealed that emigration contributes negatively to the reallocation of labor from the industrial sector. Only the total emigration rate negatively affects the reallocation of labor from the service sector. No statistical relationship exists between other emigration rates and the reallocation of labor from the service sector. ECOWAS countries should encourage policies aimed at capitalizing on the skills of emigrants through summer schools, following the example of the African Development Bank. They should also support industrial development while encouraging the agricultural production of intermediate goods for industrial production. This synergy promotes the reallocation of labor from the agricultural sector to the industrial sector and then to the service sector and leads to the structural transformation of economies, so much desired by the African Union.(original abstract)
Keywords: Emigration; Society; Structural transformation